Emergency of fungemia cases caused by fluconazole-resistant Candida auris in Beijing, China. Issue 6 (December 2018) - Chen, Yong; Zhao, Jingya; Han, Li; Qi, Lihua; Fan, Weihong; Liu, Jie; Wang, Zhigang; Xia, Xian; Chen, Jia; Zhang, Liangliang
Highlights: Candida auris with different antifungal resistance profiles has emerged in difference parts of China. Strain misidentification for Candida auris is a significant problem in Chinese hospitals. The guidelines for the control and prevention of Candida auris infections are urgently needed in Chinese hospitals. Itraconazole is effective for the treatment of fungemia cases caused by fluconazole-resistant Candida auris. Summary: We describe the microbiological characterization and clinical presentation of two fungemia cases caused by fluconazole-resistant Candida auris in neonatal intensive care unit of a hospital in Beijing, China. We advocate for the need of guidelines or recommendations to improve identification, surveillance, and implementation of infection control measures in Chinese hospitals.